Analisis Faktor Hasil Belajar Statistika Perusahaan PadaMahasiswa Program Studi PendidikanakuntansiUniversitas Muhammadiyah SurakartaAngakatan 2014 - Tri Wijanarko, Tito; , Drs. Budi Sutrisno, M.Pd (2016)
The aims of this reseach are to know: 1) The difference of learning outcome according variant of the excercises' frequency, 2) The difference of learning outcome towards students' perception of lecturer's teaching skill. 3) The interaction of variant of the excercise's frequency and the students' ofof lecturer's teaching skill toward learning outcome. This research employs quantitative comparative method. The population in this research are the 2014 Department Accounting Education students of UMS who take Company Statistics as many as 205 students with sample taken as many as 127 students using proportional random sampling technique. Data collectionn technique used in this research is using questionnaire which had been tested with two way variant analysis. Based on two way variant analysis acquired the result as follow: 1) Excercises' frequency variable (X1) is divided into three criteria, those are: a) frequent criteria between 75,91 - 82,72 as many as 46 students. b) Infrequent criteria between 54,65 - 68,82 as many as 73 students. c) Never criteria between 47,57 - 40,48 as many as 8 students. 2) Students' perception of lecturer's teaching skill variable (X2) is divided into three criteria, those are: a) Good criteria between 70,16- 74,96 as many as 43 students. b) Sufficient criteria between 55,76 - 65,36 as many as 71 students. c) Lack criteria between 50,96 - 46,16 as many as 13 students. 3) The first hypothesis trial Fhitung 7,735 probability 0,000 and Ftabel 3,919 with significancy 0,05 with the result that 7,735 >3,919 and 0,000 < 0,05 then there is a significant difference of the learning outcome viewed from excercises' frequency, 4) The second hypothesis trial Fhitung 13,248 probability 0,000 and Ftabel 3,071with significancy 0,05 with the result that 13,248 > 3,073 and 0,000 < 0,05 then there is a significant difference of the learning outcome viewed from students' perception of lecturer's teaching skill, 5) The third hypothesis trial Fhitung 14,140 probability 0,001and Ftabel 3,071with significancy 0,05 with the result that 14,140>3,071 and 0,001 < 0,05then there is an interaction between excercises' frequency and students' perception of lecturer's teaching skill toward learning outcome.